The calcium uniporter regulates the permeability transition pore in isolated cortical mitochondria★ - Yu, Ning (Neural Regen Res, 2012)
To investigate the influence of the mitochondrial calcium uniporter on the mitochondrial permeability transition pore, the present study observed mitochondrial morphology in cortical neurons isolated from adult rats using transmission electron microscopy, and confirmed the morphology and activity of isolated mitochondria by detecting succinic dehydrogenase and monoamine oxidase, two mitochondrial enzymes. Isolated mitochondria were treated with either ruthenium red, an inhibitor of the uniporter, spermine, an activator of the uniporter, or in combination with cyclosporin A, an inhibitor of the mitochondrial permeability transition pore. Results showed that ruthenium red inhibited CaCl(2)-induced mitochondrial permeability transition pore opening, spermine enhanced opening, and cyclosporin A attenuated the effects of spermine. Results demonstrated that the mitochondrial calcium uniporter plays a role in regulating the mitochondrial permeability transition pore in mitochondria isolated from the rat brain cortex.